117. Adjunctive Daptomycin in the Treatment of staphylococcus Aureus Bacteremia. (31st December 2020) - Cheng, Matthew P; Lawandi, Alexander; Butler-Laporte, Guillaume; De L'Etoile-Morel, Samuel; Paquette, Katryn; Lee, Todd C
Abstract: Background: Bloodstream infections (BSI) caused by methicillin-susceptible Staphylococcus aureus (MSSA) are associated with significant morbidity and mortality. The objective of our study was to determine whether daptomycin given in combination with an anti-staphylococcal beta-lactam improved outcomes in MSSA BSI. Methods: A randomized, double blind, placebo-controlled trial was performed at two academic hospitals in Montreal, Canada. Patients ≥ 18 years of age with MSSA BSI receiving either cefazolin or cloxacillin monotherapy were considered for inclusion. In addition to the standard of care treatment, participants received a 5-day course of adjunctive daptomycin or placebo. The primary outcome was the duration of MSSA BSI in days. Results: Of 318 participants screened, 115 were enrolled and 104 were included in the intention to treat analysis (median age 67 years; 34.5% female). The median duration of bacteremia was 2.04 days among patients who received daptomycin versus 1.65 days in those who received placebo (absolute difference 0.39 days, p=0.40). A modified intention to treat analysis involving participants who remained bacteremic at the time of enrollment found a median duration of bacteremia of 3.06 days among patients who received daptomycin versus 3.0 days in those who received placebo (absolute difference 0.06 days, p=0.77). Ninety-day mortality in the daptomycin arm was 18.9% vs. 17.7% in the placebo arm (p=1.0). There were no significant differences in the proportion of patients who developed renal failure, hepatotoxicity, or rhabdomyolysis between groups. Conclusion: Among patients with MSSA BSI, the administration of adjunctive daptomycin therapy to standard of care treatment did not shorten the duration of bacteremia. Disclosures: All Authors : No reported disclosures